1997
DOI: 10.1063/1.118218
|View full text |Cite
|
Sign up to set email alerts
|

Transport of argon ions in an inductively coupled high-density plasma reactor

Abstract: The first direct observation of the velocity distribution of the metastable Ar+*(2G9/2) ions in the presheath of an inductively coupled plasma has been achieved by using the Doppler shifted laser induced fluorescence technique. Drift of the ions along the electric field in the presheath is observed and distribution functions of the velocity in both parallel and perpendicular directions, relative to the E field, are deduced at 5 and 40 mTorr. Present results show that in high density plasmas the velocity distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 15 publications
4
40
0
Order By: Relevance
“…In the field of lowtemperature plasma research, the velocity and the corresponding kinetic energy of plasma particles is an important parameter, for instance, to determine particle and/or energy fluxes in plasma processing. Nevertheless, only a few studies exist in which the LIF technique is applied to measure velocities of particles in plasmas, 30,31 and to the best of our knowledge our group was the first to report velocity measurements of ground-state atoms using the two-photon LIF technique. 32 In this study, two-photon excitation laser-induced fluorescence is applied to perform quantitative and spatially resolved measurements of the density, temperature, and velocity of ground-state hydrogen atoms in an expanding thermal Ar-H plasma created by a cascaded arc.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of lowtemperature plasma research, the velocity and the corresponding kinetic energy of plasma particles is an important parameter, for instance, to determine particle and/or energy fluxes in plasma processing. Nevertheless, only a few studies exist in which the LIF technique is applied to measure velocities of particles in plasmas, 30,31 and to the best of our knowledge our group was the first to report velocity measurements of ground-state atoms using the two-photon LIF technique. 32 In this study, two-photon excitation laser-induced fluorescence is applied to perform quantitative and spatially resolved measurements of the density, temperature, and velocity of ground-state hydrogen atoms in an expanding thermal Ar-H plasma created by a cascaded arc.…”
Section: Introductionmentioning
confidence: 99%
“…Spatially resolved and in situ measurements of the tIVDFs were performed in various sources of plasmas [13][14][15][16][17][18][19] using the LIF technique, but some of these measurements were made at a single point in the plasma, and none were correlated with plasma potential measurements along the presheath. In the vicinity of a glass boundary plate, however, Sadeghi et al 18 measured tIVDFs at a variety of locations, which demonstrated considerable broadening ͑heating͒ as the ions transited the presheath.…”
Section: Experimental Studies Of Transverse Metastable Ion Velocity Dmentioning
confidence: 99%
“…Consequently, we can conclude that spatial potential plays an important role in ion heating. 13,21 It may be doubted that the ion temperature increases due to the relative measurement position change in the presheath when biased. However, in this experiment this bias increases the total spatial potential including sheath potential in the axial direction, …”
Section: B DC Bias Effectmentioning
confidence: 99%
“…LIF has such good spectral resolution ͑ϳ0.0025 eV ion or neutral temperature͒ 10 that many experiments on ion or neutral heating have been conducted in low-temperature processing plasmas. These efforts explained ion heating qualitatively from electron-ion collisions, 17 potential in the presheath, 13,21 and wave interaction, 18 but these were not enough to explain why ion temperature is much higher than room temperature in the center of the plasma. In this study, we have used the diode LIF scheme to measure metastable argon ion velocity distribution functions in magnetized inductively coupled plasma to obtain metastable ion density and temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation